Geographical variation in rates of surgical treatment for female stress urinary incontinence in England: a national cohort study. Issue 8 (28th August 2019) - Mamza, Jil B; Geary, Rebecca S; El-Hamamsy, Dina; Cromwell, David A; Duckett, Jonathan; Monga, Ash; Toozs-Hobson, Philip; Mahmood, Tahir; Wilson, Andrew; Tincello, Douglas G; van der Meulen, Jan H; Gurol Urganci, Ipek
Abstract : Objective: To examine geographic variation in use of surgery for female stress urinary incontinence (SUI), mainly midurethral mesh tape insertions, in the English National Health Service (NHS). Design: National cohort study. Setting: NHS hospitals. Participants: 27 997 women aged 20 years or older who had a first SUI surgery in an English NHS Hospital between April 2013 and March 2016 and a diagnosis of SUI at the same time as the procedure. Methods: Multilevel Poisson regression was used to adjust for geographic differences in age, ethnicity, prevalence of long-term illness and socioeconomic deprivation. Primary outcome measure: Rate of surgery for SUI per 100 000 women/year at two geographic levels: Clinical Commissioning Group (CCG; n=209) and Sustainability and Transformation Partnership (STP; n=44). Results: The rate of surgery for SUI was 40 procedures per 100 000 women/year. Risk-adjusted rates ranged from 20 to 106 procedures per 100 000 women/year across CCGs and 24 to 69 procedures per 100 000 women/year across the STP areas. These regional differences were only partially explained by demographic characteristics as adjustment reduced variance of surgery rates by 16% among the CCGs and 35% among the STPs. Conclusions: Substantial geographic variation exists in the use of surgery for female SUI in the English NHS, suggesting that women in some areas are more likely to be treated compared with women with the same condition in other areas. The variation reflects differences in how national guidelines are being interpreted in the context of the ongoing debate about the safety of SUI surgery.